The Separation of Thromboplastin Formed from Pig’s Plasma in the Thromboplastin Generation Test - Cross, M. J (Thrombosis and Haemostasis, 1962)
1. Plasma thromboplastin has been formed from a mixture of pigs’ plasma, serum and platelets using a modification of the thromboplastin generation system of Biggs and Douglas (1953). The thromboplastic activity in the modified system was more stable than in the original system.2. A sediment with considerable thromboplastic activity has been obtained by centrifugation. This sediment was free of platelets and contained very little thrombin.3. The sediment when resuspended in buffer was fully active only in the presence of calcium and between pH 6.6 and 7.0. The activity slowly decreased at 0—4° C and rapidly at 65° C.4. The sediment rapidly converted prothrombin to thrombin in the absence of factor V.5. The activity of the sediment was unaffected when it was incubated with thrombin.